Investigating the Phytochemical Composition, GCMS Profile and Antimicrobial Effects of Nursehan Herbal Remedy for Sinusitis in Praya, Central Lombok - Agrijanti; Lale Budi Kusumadewi; Ari Khusuma; Fathul Djannah; Siti Rahmatul Aini (Jurnal Penelitian Pendidikan IPA, 2025)
Recent studies emphasize the importance of medicinal plants in Indonesia's healthcare systems, where traditional remedies, including herbal formulations, are commonly used for treating ailments such as sinusitis. This research focuses on the Nursehan herbal remedy, a traditional treatment for sinusitis, used in Praya District, Central Lombok Regency. Nursehan is a combination of several plant materials, including Cinnamomum verum, Nauclea orientalis, and Nigella sativa, which are believed to alleviate sinus-related symptoms. However, scientific evidence supporting its efficacy remains limited. This study aims to validate the antimicrobial potential of Nursehan by analyzing its phytochemical profile and antibacterial activity. The Nursehan extract was prepared using a maceration method, and its chemical composition was assessed via GC-MS analysis, which identified key bioactive compounds such as hexadecanoic acid and 8-heptadecenoic acid, known for their antimicrobial and anti-inflammatory properties. Antimicrobial testing using the Kirby-Bauer method revealed significant antibacterial activity, particularly against Streptococcus pyogenes and Staphylococcus aureus. These findings provide scientific backing for the traditional use of Nursehan and highlight its potential as a therapeutic agent for sinusitis.